LAPORAN KASUS : OBSTRUKSI INTESTINAL TOTAL YANG DISEBABKAN OLEH ENDOMETRIOSIS INTESTINAL DAN ENDOMETRIOSIS UTERUS PADA WANITA 43 TAHUN DI RUMAH SAKIT ABDUL MOELOEK LAMPUNG - Risal Wintoko; Wina Nazula Makrufa (CV. Jasa Sukses Abadi, 2020)
Intestinal endometriosis is a disorder where the endometrium glands and stroma grow outside the uterus. Endometriosis could involve various intraperitoneal and extraperitoneal organs. Endometriosis occurs on the gastrointestinal organs in 3-15% women in reproductive age. The most common organs involved were rectosigmoid colon (71%), appendix (19%), terminal ileum (6.7%), caecum (5.5%) and transversal colon. Endometriosis mostly occurs in age group 40-44 years old (26,4%). Symptoms that usually happen in endometriosis are bleeding outside the menstrual cycle, pain during menstruation, pain during intercourse, pain during defecation, and pain during urination. In addition, usually there is pain on the hips before menstruation. Symptoms of intestinal endometriosis are pain on the abdomen and pelvis, constipation, diarrhea, enlarged abdomen, mucus in the stool, rectal bleeding, nausea, vomiting and intestinal obstruction. In this case report, a 43 years old woman with total intestinal obstruction due to intestinal endometriosis and uterine endometriosis. Patient were given laparotomy and found cystic masses in ileum, mesentrium, caecum, and uterus. Therapies given in this case are hysterectomy, resection of the terminal ileum until tranversal colon, and as well as end-to-end anastomose ileum and transversal colon. After a successful surgical therapy, hormonal suppression therapy is given to prevent recurrence.